Galvanized material surface passivation solution with heat insulation performance and coating preparation method
By adding acidic silica sol to the acid passivation solution, the problems of precipitation and adhesion of the surface passivation solution on the galvanized material are solved, and the thermal insulation and corrosion resistance of the surface passivation film on the galvanized material are achieved, achieving the effect of energy saving and emission reduction.
Patent Information
- Application Number
- CN202411938954.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-21
AI Technical Summary
The surface passivation liquid of the existing galvanized material is prone to precipitation after adding nano-silicon sol, resulting in liquid instability. The passivation film has problems such as rough surface and poor adhesion, making it difficult to achieve good thermal insulation performance.
Add acidic silica sol to the acid passivation liquid system to ensure uniform and stability of the passivation liquid, and prepare a galvanized material surface passivation liquid with thermal insulation properties through specific component ratios and stirring steps.
The stability of the passivation fluid and the thermal insulation performance of the passivation film are achieved, the corrosion resistance is not affected, and the adhesion and corrosion resistance are also met with high standards, effectively reducing the use of air conditioners in buildings and cars in summer and winter, achieving the purpose of energy conservation and emission reduction.
Smart Images

Figure CN119663261A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of metal surface treatment, in particular to the surface passivation of galvanized materials, and specifically to a galvanized material surface passivation liquid with heat insulation performance and a coating preparation method. Background Art
[0002] Chromium-free passivation is a metal surface treatment process that has developed rapidly after the promulgation of the EU RoHS directive. At present, chromium-free passivation has formed several relatively mature systems: one is inorganic component passivation, such as silicate passivation, molybdate passivation, etc.; the second is organic compound passivation, such as organic silane passivation, organic acid passivation, resin emulsion passivation, etc.; the third is inorganic-organic composite passivation, such as silane + additives, resin + additives passivation technology, etc. Among them, inorganic-organic composite passivation research and application are more extensive.
[0003] Nano-silicon dioxide, titanium dioxide or other nano-materials mostly have the functions of heat insulation and reflection, and are currently widely used in thermal insulation coatings. In the article "Preparation and Performance of Silica Sol-Pure Acrylic Composite Emulsion Reflective Thermal Insulation Coatings", scholar Lin Mei studied the reflective thermal insulation coatings prepared with silica sol and pure acrylic emulsion as composite base materials, and then adding inorganic components such as titanium dioxide and kaolin. The increase in the proportion of silica sol in the base material helps to improve the solar reflectance of the coating and the solar reflectance after pollution, and the contact angle of the coating surface to water also gradually increases. Finally, an inorganic-organic composite reflective thermal insulation coating with strong stain resistance, high heat reflection resistance and radiation resistance was prepared.
[0004] The silica sol, titanium dioxide, kaolin and other ingredients in the paint make the paint have the disadvantages of rough surface, easy cracking of the paint film, poor adhesion, etc. After construction, even irregular protruding particles are distributed partially or entirely on the surface. The metal surface passivation film requires a smooth and uniform surface with a certain gloss, and no obvious roughness or granularity. Therefore, in the experiment, a more uniform and stable nano-silica sol with a small particle size was added to the passivation solution. However, it was found in the experiment that after the addition of nano-silica sol, the entire passivation solution system would produce precipitation. In order to effectively solve this problem and achieve the stability of the passivation solution, after many experimental explorations, it was finally determined that adding acidic silica sol to the acidic passivation solution system can achieve uniform stability of the passivation solution. The prepared passivation solution is coated on the surface of the galvanized sheet to form a passivation film, which has a certain heat insulation effect. At present, there is no literature report on the research on the surface passivation solution of galvanized materials with heat insulation properties, which is of research significance. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a galvanized material surface passivation liquid with heat insulation performance and a coating preparation method, so as to form a passivation film on the surface of the galvanized material, so that the passivation film has a certain heat insulation effect by adding nano components such as nano sol while still having good anti-corrosion performance. It is expected that buildings and cars made of galvanized sheets coated with passivation films can reduce the use of electrical equipment such as air conditioners in summer and winter, so as to achieve energy saving, emission reduction and green environmental protection.
[0006] A passivation solution for the surface of galvanized materials with heat-insulating properties, wherein the contents of the components in the passivation solution are measured in grams as follows: 24.0 g of emulsion, 24.0 g of organosilane, 0.5-1.0 g of inorganic corrosion inhibitor, 0.0-12.5 g of nanosol, 60.0 g of deionized water, and a small amount of pH regulator (the mass of which can be ignored).
[0007] Furthermore, the emulsion is one or a mixture of water-based acrylic emulsion and silicone acrylic emulsion.
[0008] Furthermore, the organic silane is one or a mixture of two of silane coupling agent KH560 (γ-glycidyloxypropyltrimethoxysilane) and silane coupling agent KH602 (N-aminoethyl-3-aminopropylmethyldimethoxysilane).
[0009] Furthermore, the inorganic corrosion inhibitor is one or a mixture of sodium molybdate, sodium orthovanadate, and sodium silicate, and the three can be mixed in any proportion.
[0010] Furthermore, the nano-sol is an acidic nano-silica sol, and the SiO2 content in the acidic nano-silica sol is 30±1%.
[0011] Furthermore, the pH adjuster is a 0.1 mol / L hydrochloric acid aqueous solution.
[0012] The method for preparing a passivation liquid coating on the surface of a galvanized material having heat insulation performance comprises the following steps: Step 1: Add 24.0 g of the emulsion, 24.0 g of the silane coupling agent and 60.0 g of deionized water into a 250 ml beaker and stir magnetically for 1-2 hours; Step 2: Add 0.5-1.0 g of inorganic corrosion inhibitor to the above solution, continue magnetic stirring for 2-3 hours to fully dissolve the inorganic corrosion inhibitor, and adjust the pH value of the system to between 3-5; then add different masses of acidic silica sol solution, magnetically stir for 1-2 hours, and you can get a chromium-free passivation solution with heat insulation properties added with nano sol.
[0013] Step 3: Pour an appropriate amount of passivation liquid into the culture dish, put the cleaned galvanized sheet into the culture dish and soak it for 30 seconds, take it out and put it on the prepared iron net, and put it into the oven to dry; set the oven temperature to 90℃, bake for 3 minutes and take it out to obtain a galvanized sheet with a passivation film attached to the surface.
[0014] Furthermore, in step 3, the galvanized sheet is pretreated to clean the surface oil stains, the galvanized sheet is placed in an ultrasonic cleaner for cleaning, taken out, wiped dry and washed with acetone, and then soaked in a mixed alkaline solution of sodium hydroxide and sodium silicate, taken out, rinsed repeatedly with deionized water, and wiped dry for later use.
[0015] Beneficial effects of the present invention: 1. The present invention achieves the heat insulation performance of the passivation film by adding acidic nano-silica sol. According to experimental tests, the anti-corrosion performance of the passivation film with the addition of acidic nano-silica sol is not significantly disturbed. In the 5% copper sulfate solution drip test, no blackening occurs after 20 minutes; the adhesion of the passivation film in the cross-cutting test can reach level 1, and the corrosion area in the neutral salt spray test for 48 hours is less than 5%. In the light insulation performance test, the passivation film with the addition of acidic silica sol can reduce the temperature rise by 4.7 °C within 30 minutes compared with the galvanized sheet that has only undergone surface pretreatment, and can reduce the temperature rise by 2.5 °C within 30 minutes compared with the passivation film of the galvanized sheet without acidic silica sol. It can be seen that the passivation film has a relatively obvious heat insulation effect under the premise of having both anti-corrosion performance.
[0016] 2. In order to prevent precipitation of the entire passivation liquid system after the addition of nano-silica sol, the present invention adopts the method of adding acidic silica sol into the acidic passivation liquid system to achieve uniform and stable passivation liquid.
[0017] 3. The prepared passivation liquid is coated on the surface of the galvanized sheet to form a passivation film, so as to achieve the best thermal insulation performance of the passivation film. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 , thermal insulation performance testing device; Figure 2 , 30min temperature difference comparison diagram of silica sol passivation films with different contents in Examples 1-6 of the present invention. DETAILED DESCRIPTION
[0019] The present invention is further explained below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the following specific embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. It should be noted that the words "front", "rear", "left", "right", "upper" and "lower" used in the following description refer to directions in the accompanying drawings, and the words "inner" and "outer" refer to directions toward or away from the geometric center of a specific component, respectively. Example
[0020] Each component of the prepared passivation solution is calculated in grams (g), and the specific amount of each component is as follows: Lotion 24.0g Organosilane 24.0g Inorganic corrosion inhibitor 0.8g Nanosol 0.0g Deionized water 60.0g pH adjuster small amount The specific method of this embodiment is as follows: Add 24.0g acrylic emulsion, 24.0g silane coupling agent KH560 and 60.0g deionized water into a 250ml beaker and stir magnetically for 1.5h; add 0.8g sodium molybdate to the above solution and continue to stir magnetically for 2h to fully dissolve the inorganic corrosion inhibitor and adjust the pH value of the system to between 3-5; and a chromium-free passivation solution is obtained (no acidic silica sol is added in Example 1).
[0021] Pour an appropriate amount of passivation liquid into a petri dish, soak the cleaned galvanized sheet in the petri dish for 30 seconds, take it out and place it on the prepared iron net, and put it in an oven to dry. Set the oven temperature to 90℃, bake for 3 minutes, and take it out to get a galvanized sheet with a passivation film on the surface for testing. Example
[0022] Each component of the prepared passivation solution is calculated in grams (g), and the specific amount of each component is as follows: Lotion 24.0g Organosilane 24.0g Inorganic corrosion inhibitor 0.8g Nanosol 2.5g Deionized water 60.0g pH adjuster small amount The specific method of this embodiment is as follows: Add 24.0g acrylic emulsion, 24.0g silane coupling agent KH560 and 60.0g deionized water into a 250ml beaker and stir magnetically for 1.5h; add 0.8g sodium molybdate to the above solution and continue to stir magnetically for 2h to fully dissolve the inorganic corrosion inhibitor and adjust the pH value of the system to between 3-5; then add 2.5g acidic silica sol solution and stir magnetically for 1.5 hours to obtain a chromium-free passivation solution with heat insulation properties with the addition of nanosol.
[0023] Pour an appropriate amount of passivation liquid into a petri dish, soak the cleaned galvanized sheet in the petri dish for 30 seconds, take it out and place it on the prepared iron net, and put it in an oven to dry. Set the oven temperature to 90℃, bake for 3 minutes, and take it out to get a galvanized sheet with a passivation film on the surface for testing. Example
[0024] Each component of the prepared passivation solution is calculated in grams (g), and the specific amount of each component is as follows: Lotion 24.0g Organosilane 24.0g Inorganic corrosion inhibitor 0.8g Nanosol 5.0g Deionized water 60.0g pH adjuster small amount The specific method of this embodiment is as follows: Add 24.0g acrylic emulsion, 24.0g silane coupling agent KH560 and 60.0g deionized water into a 250ml beaker and stir magnetically for 1.5h; add 0.8g sodium molybdate to the above solution and continue to stir magnetically for 2h to fully dissolve the inorganic corrosion inhibitor and adjust the pH value of the system to between 3-5; then add 5.0g acidic silica sol solution and stir magnetically for 1.5 hours to obtain a chromium-free passivation solution with heat insulation properties added with nanosol.
[0025] Pour an appropriate amount of passivation liquid into a petri dish, soak the cleaned galvanized sheet in the petri dish for 30 seconds, take it out and place it on the prepared iron net, and put it in an oven to dry. Set the oven temperature to 90℃, bake for 3 minutes, and take it out to get a galvanized sheet with a passivation film on the surface for testing. Example
[0026] Each component of the prepared passivation solution is calculated in grams (g), and the specific amount of each component is as follows: Lotion 24.0g Organosilane 24.0g Inorganic corrosion inhibitor 0.8g Nanosol 7.5g Deionized water 60.0 pH adjuster small amount The specific method of this embodiment is as follows: Add 24.0g acrylic emulsion, 24.0g silane coupling agent KH560 and 60.0g deionized water into a 250ml beaker and stir magnetically for 1.5h; add 0.8g sodium molybdate to the above solution and continue to stir magnetically for 2h to fully dissolve the inorganic corrosion inhibitor and adjust the pH value of the system to between 3-5; then add 7.5g acidic silica sol solution and stir magnetically for 1.5 hours to obtain a chromium-free passivation solution with heat insulation properties with the addition of nanosol.
[0027] Pour an appropriate amount of passivation liquid into a petri dish, soak the cleaned galvanized sheet in the petri dish for 30 seconds, take it out and place it on the prepared iron net, and put it in an oven to dry. Set the oven temperature to 90℃, bake for 3 minutes, and take it out to get a galvanized sheet with a passivation film on the surface for testing. Example
[0028] Each component of the prepared passivation solution is calculated in grams (g), and the specific amount of each component is as follows: Lotion 24.0g Organosilane 24.0g Inorganic corrosion inhibitor 0.8g Nanosol 10.0g Deionized water 60.0g pH adjuster small amount The specific method of this embodiment is as follows: Add 24.0g acrylic emulsion, 24.0g silane coupling agent KH560 and 60.0g deionized water into a 250ml beaker and stir magnetically for 1.5h; add 0.8g sodium molybdate to the above solution and continue to stir magnetically for 2h to fully dissolve the inorganic corrosion inhibitor and adjust the pH value of the system to between 3-5; then add 10.0g acidic silica sol solution and stir magnetically for 1.5 hours to obtain a chromium-free passivation solution with heat insulation properties with the addition of nanosol.
[0029] Pour an appropriate amount of passivation liquid into a petri dish, soak the cleaned galvanized sheet in the petri dish for 30 seconds, take it out and place it on the prepared iron net, and put it in an oven to dry. Set the oven temperature to 90℃, bake for 3 minutes, and take it out to get a galvanized sheet with a passivation film on the surface for testing. Example
[0030] Each component of the prepared passivation solution is calculated in grams (g), and the specific amount of each component is as follows: Lotion 24.0g Organosilane 24.0g Inorganic corrosion inhibitor 0.8g Nanosol 12.5g Deionized water 60.0g pH adjuster small amount The specific method of this embodiment is as follows: Add 24.0g acrylic emulsion, 24.0g silane coupling agent KH560 and 60.0g deionized water into a 250ml beaker and stir magnetically for 1.5h; add 0.8g sodium molybdate to the above solution and continue to stir magnetically for 2h to fully dissolve the inorganic corrosion inhibitor and adjust the pH value of the system to between 3-5; then add 12.5g acidic silica sol solution and stir magnetically for 1.5 hours to obtain a chromium-free passivation solution with heat insulation properties added with nanosol.
[0031] Pour an appropriate amount of passivation liquid into a petri dish, soak the cleaned galvanized sheet in the petri dish for 30 seconds, take it out and place it on the prepared iron net, and put it in an oven to dry. Set the oven temperature to 90℃, bake for 3 minutes, and take it out to get a galvanized sheet with a passivation film on the surface for testing.
[0032] In the passivation solution formulas of Examples 1-6, except for the different addition amounts of acidic nano-silica sol, the amounts of other components, stirring time, passivation time, and drying time are all the same. The purpose is to only change the addition amount of acidic silica sol to test the effect of its addition amount in the passivation solution on the thermal insulation performance.
[0033] The heat insulation performance of the chromium-free passivation film on the surface of the galvanized sheet of the present invention is tested on the premise that the passivation film has good anti-corrosion performance. The corrosion resistance of the passivation film is mainly tested by copper sulfate dripping, neutral salt spray, and salt water immersion experiments; at the same time, the adhesion, solvent resistance, and alkali resistance of the film layer also need to be tested; the above tests are all tested in accordance with the methods specified in the national standard; and the heat insulation performance test is carried out in a self-made light box, according to Figure 1 The device was used to irradiate the galvanized sheet with a passivation film on the surface with an infrared lamp for 30 minutes in a closed heat-insulated environment, and the blank galvanized sheet that had only been surface cleaned was irradiated in the same way for 30 minutes as a blank comparison. The temperature was recorded every 3 minutes. According to a total of 7 groups of tests between the blank and Examples 1-6, a temperature difference comparison chart was made for the difference in temperature change within 30 minutes, as shown in FIG. Figure 2 shown.
[0034] Depend on Figure 2 It can be seen that when the amount of acidic silica sol added is 10.0 g (ie, Example 5), the thermal insulation effect is the best. After 30 minutes of illumination, the temperature rises by 14.0°C, which is 4.7°C less than that of the blank galvanized sheet that has only been pretreated, and 2.5°C less than that of the galvanized sheet passivation film without acidic silica sol (ie, Example 1). It can be seen that the thermal insulation performance of the passivation film is directly related to the content of acidic nano-silica sol, but the thermal insulation performance will deteriorate as the amount added increases.
[0035] When the emulsion is replaced with a silicone-acrylic emulsion, the 30-minute temperature change still has the above trend, but compared with the temperature rise of the blank galvanized sheet, the amount of acidic silica sol added when the maximum temperature difference occurs is different. At the same time, the emulsion in the component can also be replaced with water-soluble biopolysaccharides, such as chicory polysaccharide, chitosan, and shellac for experiments, and the type of silane coupling agent can be changed, and similar experimental results will also appear.
[0036] The technical means disclosed in the scheme of the present invention are not limited to the technical means disclosed in the above-mentioned implementation mode, but also include technical schemes composed of any combination of the above technical features.
Claims
1. A galvanized material surface passivation solution with heat insulation performance, characterized in that: The contents of the components in the passivation solution are measured in grams as follows: 24.0 g of emulsion, 24.0 g of organosilane, 0.5-1.0 g of inorganic corrosion inhibitor, 0.0-12.5 g of acidic nanosol, 60.0 g of deionized water, and a pH regulator.
2. The surface passivation solution for galvanized materials with heat insulation performance according to claim 1, characterized in that: The emulsion is one or a mixture of water-based acrylic emulsion and silicone acrylic emulsion, and the mixing mass ratio of the two is 2-3:
1.
3. The surface passivation solution for galvanized materials with heat insulation performance according to claim 1, characterized in that: The organic silane is one of silane coupling agent KH560 and silane coupling agent KH602 or a mixture of the two, and the mass ratio of the two is 2-4:
1.
4. The surface passivation solution for galvanized materials with heat insulation performance according to claim 1, characterized in that: The inorganic corrosion inhibitor is one or a mixture of sodium molybdate, sodium orthovanadate and sodium silicate, and the three can be mixed in any proportion.
5. The surface passivation solution for galvanized materials with heat insulation performance according to claim 1, characterized in that: The nano sol is acidic nano silica sol.
6. The surface passivation solution for galvanized materials with heat insulation performance according to claim 5, characterized in that: The SiO2 content in the acidic nano-silica sol is 30±1%.
7. The surface passivation solution for galvanized materials with heat insulation performance according to claim 1, characterized in that: The pH adjuster is a 0.1 mol / L hydrochloric acid aqueous solution.
8. A method for preparing a passivation liquid coating on the surface of a galvanized material having heat-insulating properties, characterized in that: The following steps are involved: Step 1: Add 24.0 g of the emulsion, 24.0 g of the silane coupling agent and 60.0 g of deionized water into a 250 ml beaker and stir magnetically for 1-2 hours; Step 2: Add 0.5-1.0g of inorganic corrosion inhibitor to the above solution, continue magnetic stirring for 2-3 hours to fully dissolve the inorganic corrosion inhibitor, and adjust the pH value of the system to between 3-5; then add different masses of acidic silica sol solution, and magnetically stir for 1-2 hours to obtain a chromium-free passivation solution with heat insulation performance; Step 3: Pour an appropriate amount of passivation liquid into the culture dish, put the cleaned galvanized sheet into the culture dish and soak it for 30 seconds, take it out and put it on the prepared iron net, and put it into the oven to dry; set the oven temperature to 90℃, bake for 3 minutes and take it out to obtain a galvanized sheet with a passivation film attached to the surface.
9. The method for preparing a passivation liquid coating on the surface of a galvanized material having heat-insulating properties according to claim 8, characterized in that: In step 3, the galvanized sheet is pretreated to clean the surface oil stains, the galvanized sheet is placed in an ultrasonic cleaner for cleaning, taken out, wiped dry and washed with acetone, and then soaked in a mixed alkaline solution of sodium hydroxide and sodium silicate, taken out, rinsed repeatedly with deionized water, and wiped dry for later use.